One more step in the study of children’s daily stress: The spillover effect as the transfer of tension in family and school environments - Infante-Cañete, Lidia; Arias-Calero, Lidia; Wallace-Ruiz, Agustin; Sánchez-Sánchez, Ana María; Muñoz-Sánchez, Ángela (Frontiers in Psychology, 2022)
The spillover effect is defined as the psychological overflow due to daily stress in one context, and the transfer of its consequences to another nearby environment. The aim is to explore the spillover effect in conflicts within the family and school conflicts with peers as an inferred measure of daily stress, according to the literature. The study consisted of a sample of 208 6-year-old students and their families. The methodology used is based on daily report records, via two ad hoc checklists with simultaneous measures during two consecutive weeks and three academic years for both family and school contexts. A repeated measures design and a nonparametric statistical data analysis with the Friedman test and contrast measures have been used. It has been proven there is bidirectionality in the spillover effect between the family and the school contexts, although this spillover effect is connected to certain moments and events. The data also provide a characteristic behavioral pattern indicating the most conflictive days and the times of the day which are associated with subsequent conflictive episodes. The sociocultural level has not been a protective factor against the transfer of stress. The findings suggest further research on the impact that conflictive moments may have on the psychological and emotional development of the children, as well as their implication in other areas of their lives, through the interrelation of the different contexts.